Case report: Remarkable response to sintilimab, lenvatinib, and nab-paclitaxel in postoperative metastatic chemotherapy-resistant combined hepatocellular-cholangiocarcinoma - Zhou, Nan; Lei, Chuan-Fen; Tan, Si-Rui; Huang, Qi-Yue; Zhang, Shun-Yu; Liang, Zheng-Xin; Gou, Hong-Feng (Frontiers in Pharmacology, 2023)
Background: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a highly aggressive malignancy with a poor prognosis. However, there are no consensus treatment guidelines, and decisions are usually extrapolated from intrahepatic cholangiocarcinoma (ICC) or hepatocellular carcinoma (HCC). Given that cHCC-CCA owns the unequivocal presence of both hepatocytic and cholangiocytic differentiation, a combination regimen of anti-PD1 antibody, multikinase inhibitor, and chemotherapy targeting against both components might be an optimal choice. Case presentation: We present the case of a patient with postoperative metastatic chemotherapy-resistant cHCC-CCA who exhibited a durable response and reasonable tolerability to a combination therapy consisting of the anti-PD1 antibody sintilimab, multikinase inhibitor lenvatinib, and nab-paclitaxel, despite having a low tumor mutational burden (TMB-L), microsatellite stability (MSS), and negative programmed cell death 1 ligand 1 (PD-L1). Conclusion: The combination regimen of immune checkpoint inhibitor sintilimab, multikinase inhibitor lenvatinib, and chemotherapy with nab-paclitaxel, which targets both the HCC and ICC components, may represent a promising treatment option for patients with cHCC-CCA. Further research is warranted to validate these findings in larger patient cohorts.